Modeling of the Influence of Operational Parameters on Tire Lateral Dynamics - Alcázar-Vargas, Manuel Gonzalo; Pérez-Fernández, Javier; Sánchez-Andrades, Ignacio; Cabrera-Carrillo, Juan Antonio; Castillo-Aguilar, Juan Jesús (IOAP-MPDI, 2022)
Tires play a critical role in vehicle safety. Proper modeling of tire–road interaction is essential for optimal performance of active safety systems. This work studies the influence of temperature, longitudinal vehicle speed, steering frequency, vertical load, and inflation pressure on lateral tire dynamics. To this end, a tire test bench that allows the accurate control of these parameters and the measurement of the variables of interest was used. The obtained results made it possible to propose a simple model that allowed the determination of relaxation length as a function of tire vertical load and vehicle linear speed, and the determination of a representative tread temperature. Additionally, a model has been proposed to determine the lateral friction coefficient from the aforementioned temperature. Finally, results also showed that some variables had little influence on the parameters that characterize lateral dynamics
Keywords: vehiculos; Vehicle dynamics; Tire model; Thermal tire model; Transient tire model; Relaxation length